Avaliação das necessidades hídricas de uma cultura de gladíolos através de métodos climatológicos - Klar, A.E.; Mattos, J. R; Ranzani, G. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Water requirements for gladioli was studied by means of field experiments in which water was supplied by the furrow irrigation method. Climatological methods were used to evaluate the water need of this crop. Good trials were conducted on a Luiz de Queiroz soil series. Four treatments were used in which soil water potential was maintained at a minimum of -0.5, -1.0, -6.0 and -15.0 bars. Soil moisture content was controlled gravimetrically. The results obtained led to the following main conclusions: a) Soil water potentials over -1,0 bar resulted in better development of floral stem and vegetative growth. The formation of corms was favored by the -15.0 bars treatment. A relationship was found to exist between early flowering and increasing available water; b) The crop showed a decrease in evapotranspiration with a decrease in soil moisture potential. The determination of the ratio of actual evapotranspiration to potential evapotranspiration was rated as follous. Penman (K = 0.74), class “A” (K = 0,66); Penman-Bavel (K = 1.09), Blaney-Criddle (K = 0.61) for the treatment in which the minimum soil moisture potential was -0.5 bar and in the cycle of the crop. The potential evapotranspiration calculated according to Thornthwaite´s formula did not correlate with the actual evapotranspiration.